The Effects of a systemic insecticide on stretching and production of wax in domestic bees Apis mellifera intermissa in Northen Africa (Algeria) - TOUDERT-DJOUBER, FATIMA; Plou, V; Amrane, R; Treilhou, M (African Entomology, 2022)
Imidacloprid is a well-known systemic insecticide which has a deleterious impact on honeybees. Beekeepers in the Tizi-Ouzou wilaya (Algeria) where the imidacloprid insecticide is used, report unusual losses and deaths of bee colonies. Even at sublethal doses, insecticid can impact the most crucial tasks of a bee colony such as comb building. This study was conducted in order to investigate the effect of an imidacloprid based insecticide (Confidor®Supra) on the production of wax by the honeybee Apis mellifera intermissa. After the imidacloprid LD50 was determined in controlled conditions, three sublethal doses were tested. The mortality, the syrup consumption and the weight of the wax generated were recorded.The imidacloprid insecticide LD50 at 48 hours was evaluated at 3.5 ng.per bee on 4 days old spring worker bees. We found that the three sublethal doses (0.175 mg.L-1, 0.087 mg.L-1 and 0.035 mg.L-1) had an impact on the syrup consumption and the wax production by adult bees. Bees exposed to sublethal doses of insecticide consumed less syrup and produced less wax that the control bees. A dose response was observed regarding the production of wax.The reduction of wax production by bees caused by an exposure to an imidacloprid based insecticide ads up to the many other effects of imidacloprid described in the literature.  This kind of impact could have harmful consequences for bee colonies as wax production is the basis of nest building. The physiological causes of the reduction of wax production remain to be investigated.